2021
DOI: 10.1136/jitc-2021-003293
|View full text |Cite
|
Sign up to set email alerts
|

Selective IL-1 activity on CD8+ T cells empowers antitumor immunity and synergizes with neovasculature-targeted TNF for full tumor eradication

Abstract: BackgroundClinical success of therapeutic cancer vaccines depends on the ability to mount strong and durable antitumor T cell responses. To achieve this, potent cellular adjuvants are highly needed. Interleukin-1β (IL-1β) acts on CD8+ T cells and promotes their expansion and effector differentiation, but toxicity and undesired tumor-promoting side effects hamper efficient clinical application of this cytokine.MethodsThis ‘cytokine problem’ can be solved by use of AcTakines (Activity-on-Target cytokines), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…IL-1β is a hallmark cytokine of tissue inflammation ( 39 , 40 ) and particularly connected to T cell stimulating properties ( 41 43 ). Therefore, this cytokine was already used in several studies as adjuvant for example as mucosal adjuvant in flu vaccinations ( 16 , 44 ) or as T cell stimulus in cancer vaccines ( 45 47 ). IPS-1 was chosen as adjuvant candidate since the retinoic acid inducible gene I (RIG-I)-IPS-1 pathway plays an important role in innate immune sensing of viral infections including RSV ( 48 50 ) and the subsequent activation of adaptive immune responses ( 51 , 52 ) as exploited by the co-application of RIG-I agonists in vaccination settings ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β is a hallmark cytokine of tissue inflammation ( 39 , 40 ) and particularly connected to T cell stimulating properties ( 41 43 ). Therefore, this cytokine was already used in several studies as adjuvant for example as mucosal adjuvant in flu vaccinations ( 16 , 44 ) or as T cell stimulus in cancer vaccines ( 45 47 ). IPS-1 was chosen as adjuvant candidate since the retinoic acid inducible gene I (RIG-I)-IPS-1 pathway plays an important role in innate immune sensing of viral infections including RSV ( 48 50 ) and the subsequent activation of adaptive immune responses ( 51 , 52 ) as exploited by the co-application of RIG-I agonists in vaccination settings ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, HaCaT cells were stimulated with 1 μg/mL LPS for 24 h after treatment with the LK5 herbal complex at each concentration for 1 h. The LK5 herbal complex reduced NO production in a concentration-dependent manner and inhibited the expression of iNOS mRNA, which is involved in NO production and synthesis ( Figure 3 B,C). LPS is known to stimulate the production of inflammatory cytokines such as TNF-α, IL-1β, and IL-6 [ 37 , 38 , 39 ]. Therefore, we investigated whether the LK5 herbal complex inhibits inflammatory cytokine production.…”
Section: Resultsmentioning
confidence: 99%
“…This study observed the anti-inflammatory properties of the LK5 herbal complex in HaCaT cells stimulated with LPS and IL-4/IL-13. Inflammatory cytokines such as TNF-α, IL-6, and IL-1β are increased by LPS, which is known to promote inflammatory responses such as vasodilation and immune cell migration [ 37 , 38 , 39 ]. Recently, studies have shown that these cytokines can regulate the transcription factor STAT, which expresses several inflammatory genes [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…As outlined above, there is ample evidence to suggest that cytokine networks govern immune evasion and foster the development of immunosuppressive T cells and TAMs within the TME ( Van Den Eeckhout et al, 2021 ; Van Den Eeckhout et al, 2020 ). However, it is still unclear how to tackle the TME cytokine milieu therapeutically in order to trigger strong and sustained antitumor responses in the majority of patients.…”
Section: New and Advanced Approaches To Study The Tmementioning
confidence: 99%